Fungicidas e efeitos fisiológicos na cultura do café conilon - Herzog, Thaisa Thomazini (2017)
The State of Espirito Santo is featured in national coffee conilon production, being the activity of great importance in economic and social terms. Among the main problems faced by coffee producers include diseases, as rust of coffee, responsable for expressive losses in productivity. Associated with the other control strategies, the fungicides, are used to reduce fungal diseases to levels that do not interfere with the quality and quantity of agricultural production. Some fungicides also interfere with plant physiology.The fungicides that have physiological effects can bring benefits to the coffee crop because they present this double action However, these effects are still for a few clarified for conilon coffee crop. Before the exposed, the objective were to evaluate the control of conilon coffee rust and the physiological effects on the culture resulting from the isolated application and in combination with other active principles of epoxiconazole and pyraclostrobin. The experiment was design in radom blocks with six treatments and four replicates (two applications of pyraclostrobin and epoxiconazole + boscalid and two applications of pyraclostrobin and epoxiconazole - T1; three applications of pyraclostrobin and epoxiconazole – T2; pyraclostrobin, epoxiconazole and fluxapyroxad - T3; epoxiconazole - T4 and pyraclostrobin - T5 and, without application of fungicide - T6) and four replicates. Evaluations of rust progress were carried out; growth of branches, number of nodes per branch and length of internodes; relative index of chlorophyll; average number of rosettes with fruits, fruits per branch and fruits per rosette and productivity. The differences observed in some treatmentes were inherent to the effect of the products on the physiology of conilon coffee, since the disease was naturally controlled. As the occurrence of the disease in the field was not observed, due to unfavorable climatic conditions, the differences observed in some evaluations were inherent to the effect of the products on the physiology of conilon coffee. Based on the results obtained in the work, it was concluded that the application with epoxiconazole provided lower cumulative growth and number of nodes per plagiotropic branch, and lower number of rosettes with fruits. The treatments with pyraclostrobin positively influenced the relative chlorophyll indices x and provided lower values of the chlorophyll a/b ratio. There was no effect of the products in conilon coffee culture in the other monitored variables.